2023
DOI: 10.31235/osf.io/h2fa7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Gendered Effects of COVID-19 on Well-being: A Household Perspective

Abstract: We investigate the causal effect of COVID-19 incidence rates on changes in subjective well-being. Specifically, we employ a household-level perspective and expect that household composition (i.e., single and multi-person households and caregiving duties for children or older adults) and affluence (i.e., housing quality and financial resources) moderate the effect of COVID-19 incidence rates, with a special focus on gender differences. Employing longitudinal household data from the Panel Labour Market and Socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Regarding gender, the expectations are less straightforward. Research on gendered COVID-19 effects indicates that declines in wellbeing were primarily observed among women with caregiving responsibilities (Patzina et al, 2023;Zoch et al, 2022), an argument that appears to be less applicable to high school students. However, Zoch et al (2022) also demonstrated that women were more concerned about the various threats posed by the crisis and, furthermore, experienced higher levels of loneliness compared to men.…”
Section: Heterogeneity In the Development Of Well-beingmentioning
confidence: 99%
“…Regarding gender, the expectations are less straightforward. Research on gendered COVID-19 effects indicates that declines in wellbeing were primarily observed among women with caregiving responsibilities (Patzina et al, 2023;Zoch et al, 2022), an argument that appears to be less applicable to high school students. However, Zoch et al (2022) also demonstrated that women were more concerned about the various threats posed by the crisis and, furthermore, experienced higher levels of loneliness compared to men.…”
Section: Heterogeneity In the Development Of Well-beingmentioning
confidence: 99%